2017
DOI: 10.1186/s12944-017-0607-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus inhibits the in vivo and in vitro synthesis and secretion of apolipoprotein C3

Abstract: BackgroundHepatitis B virus (HBV) infection in the body can damage liver cells and cause disorders in blood lipid metabolism. Apolipoprotein C3 (ApoC3) plays an important role in the regulation of lipid metabolism, but no study on the HBV regulation of ApoC3 has been reported. This purpose of this study was to investigate the effect of HBV on ApoC3 expression and its regulatory mechanism.MethodsThe expression levels of ApoC3 mRNA and protein in the human hepatoma cell lines HepG2 and HepG2.2.15 were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Previous study has clearly shown that a decrease in ApoC3 is associated with a significant decrease in TG levels [25]. It is indicated that HBV down-regulated the synthesis and secretion of ApoC3 via its X gene and lower serum levels of ApoC3 and TG were observed in CHB patients [15]. In our study, we found that serum ApoC3 and TG levels in CHB patients were decreased, which is in accordance with the above results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous study has clearly shown that a decrease in ApoC3 is associated with a significant decrease in TG levels [25]. It is indicated that HBV down-regulated the synthesis and secretion of ApoC3 via its X gene and lower serum levels of ApoC3 and TG were observed in CHB patients [15]. In our study, we found that serum ApoC3 and TG levels in CHB patients were decreased, which is in accordance with the above results.…”
Section: Discussionsupporting
confidence: 91%
“…ApoC3 and ApoA5 are associated with multiple lipid metabolism-related diseases, such as type 1 diabetes and coronary artery disease [1113]. Although previous study showed that HBV inhibits ApoA5 and ApoC3 promoter activity and mRNA and protein expression through its core gene [14] or X gene [15], respectively, little was revealed about the association between ApoC3 or ApoA5 and HBV replication rate in CHB patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocytes are the major sites of apolipoprotein synthesis and lipoprotein assembly, secretion, uptake, and catabolism. Some clinical studies in HBV-infected population have found significantly decreased levels of plasma ApoA1 (Jiang et al, 2014;Wang Y. et al, 2016;Cui et al, 2019), ApoA5 (Zhu et al, 2016;Cui et al, 2019), ApoB (Wang et al, 2011;Cui et al, 2019), and ApoC3 (Zhu et al, 2017;Cui et al, 2019), whereas dramatically increased level of serum ApoM or ApoE (Gu et al, 2011;Shen et al, 2016). These results from clinical studies were consistent with observations from several experimental studies.…”
Section: The Effect Of Hbv On Apolipoprotein Metabolism In Hepatocytessupporting
confidence: 87%
“…ApoC3 acted as an inhibitor of lipoprotein lipase (LPL), which was a crucial enzyme in TG lipoprotein catabolism ( Larsson et al, 2017 ). A study ( Zhu et al, 2017 ) showed that HBV inhibited the synthesis and secretion of ApoC3. Therefore, during chronic HBV infection, a decrease in ApoC3 expression would increase LPL activity, decrease VLDL synthesis and secretion, and increase TG decomposition.…”
Section: The Effect Of Hbv On Apolipoprotein Metabolism In Hepatocytementioning
confidence: 99%
“…Our findings reinforce those of previous studies demonstrating that HBV infection is negatively associated with hypertriglyceridemia [26] and provide evidence that HBV infection negates the promoting effect of IR on TG levels. One possible mechanism explaining this phenomenon is that HBV products, including HBV protein X, interrupt de-novo lipid synthesis and secretion under insulin-resistant conditions, which are characterized by inhibition of Apo-C3 expression [27] and Apo-B secretion [28]. As the major protein component of triglyceride (TG)-rich lipoproteins, decreased Apo-B and Apo-C3 concentrations therefore lower serum very-low-density lipoprotein (VLDL) and TG levels.…”
Section: Discussionmentioning
confidence: 99%